2017
DOI: 10.1002/2017sw001691
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Geomagnetically Induced Current Observations From New Zealand: Peak Current Estimates for Extreme Geomagnetic Storms

Abstract: Geomagnetically induced current (GIC) observations made in New Zealand over 14 years show induction effects associated with a rapidly varying horizontal magnetic field (dBH/dt) during geomagnetic storms. This study analyzes the GIC observations in order to estimate the impact of extreme storms as a hazard to the power system in New Zealand. Analysis is undertaken of GIC in transformer number six in Islington, Christchurch (ISL M6), which had the highest observed currents during the 6 November 2001 storm. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(114 citation statements)
references
References 40 publications
13
101
0
Order By: Relevance
“…Comparisons of the modeled GICs in this study with observations of GICs made by Transpower (Rodger et al, ) show a reasonable agreement with the reported typical relationship between GIC magnitude at HWBT4L and ISLT6H. Rodger et al () compared the observed GICs at ISLT6 and HWBT4 during five large space weather events occurring between 17 March 2013 and 22 June 2015. In these events the peak GIC flowing through HWBT4 was ~3 times that flowing through ISLT6H.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Comparisons of the modeled GICs in this study with observations of GICs made by Transpower (Rodger et al, ) show a reasonable agreement with the reported typical relationship between GIC magnitude at HWBT4L and ISLT6H. Rodger et al () compared the observed GICs at ISLT6 and HWBT4 during five large space weather events occurring between 17 March 2013 and 22 June 2015. In these events the peak GIC flowing through HWBT4 was ~3 times that flowing through ISLT6H.…”
Section: Discussionsupporting
confidence: 87%
“…We have focused on key locations that Manus Mac et al () and Rodger et al () report as having high levels of observed GICs and have experienced documented disruption during geomagnetic storms in the past (Marshall et al, ). Transformer number 6 at ISL (ISLT6) shows relatively high observed GICs during geomagnetic storms.…”
Section: Method: Developing a Transformer‐level Gic Network Representmentioning
confidence: 99%
See 3 more Smart Citations